KAJIAN HUKUM PIDANA TERHADAP NOTARIS YANG MEMBUAT PERJANJIAN PENGIKATAN TANPA DISERTAI SURAT-SURAT BUKTI KEPEMILIKAN (Studi Kasus Putusan Nomor 1362/Pid.B/2019/PN Jkt.Utr) - Nurijah Ibrahim; Prof. Triono Eddy; Dr. Mahmud Mulyadi (Jurnal Ilmiah Advokasi, 2021)
In practice, buying and selling transactions must meet the requirements according to legal provisions, especially now that there are many buying and selling problems that result in the emergence of disputes that cause losses incurred by the seller and the buyer as well as the notary as the deed maker. The problem in this research is to research and analyze the arrangements in making the Sale and Purchase Deed (PPJB), criminal forms related to the position of a notary in making the Sale and Purchase Deed and criminal law analysis of the Notary who makes the Sale and Purchase Deed) without being accompanied proof of ownership letters in decision Number 1362 / Pid.B / 2019 / PN Jkt.Utr.Keywords: Criminal Law, Notary, Binding Agreement